Effects of starch addition amount on microstructure, mechanical properties and room temperature thermal conductivity of porous Y2SiO5 ceramics. Issue 2 (1st February 2016) - He, Rujie; Qu, Zhaoliang; Cheng, Xiangmeng
Abstract: Y2 SiO5 ceramics were prepared by dry pressing and pressureless sintering using different amount of starch addition as pore-forming agent. With the starch addition amount increases from 10 to 40 wt%, the relative density for porous Y2 SiO5 ceramics ranges from 70.4% to 38.3%, the mean pore size ranges from 1.02 to 2.01 μm, the compressive strength ranges from 28.25 to 1.43 MPa, and the room temperature thermal conductivities ranges from 0.81 to 0.18 W/m K. The relatively high strength and low thermal conductivity of porous Y2 SiO5 ceramics are believed to be useful for future high-temperature insulating applications.